PERBANDINGAN KUALITAS CITRA CT SCAN PADA PROTOKOL DOSIS TINGGI DAN DOSIS RENDAH UNTUK PEMERIKSAAN KEPALA PASIEN DEWASA DAN ANAK - Rozanah Rozanah; Wahyu Setia Budi; Zaenal Arifin (Youngster Physics Journal, 2015)
The use of scaning protocol with high dose and low dose in CT scan would affect the quality of the images obtained. Because of the importance of good radiographic images in the enforcement of proper patient diagnosis, then performed an analysis of the image quality obtained from both protocols.Image quality assessment of high-dose protocols and low doses for routine head examinations carried out through performance analysis using the AAPM CT phantom performance, comparison of the value of GM conspicuity and Contrast to Noise Ratio (CNR) of the image of the patient as well as comparison of gray scale images through image histogram comparison phantom homogeneous and patient image histogram.Results of analysis of the performance of the two protocols by assessing the accuracy of the CT number, noise, low contrast resolution and spatial resolution showed that high-dose protocol has better performance than low-dose protocol. Image with high-dose protocol has an average GM conspicuity of 0.3863 and CNR 7.0105, while the image with a low dose of 0.4144 and 6.2725 at CNR. Comparison of gray scale image of the protocol through the image histogram comparison homogeneous phantom and patient image shows that the image of a low-dose protocol has variation of intensity gray value that is wider than high-dose protocol.Keywords: Computed Tomography, scaning protocol, image quality, GM conspicuity, CNR